Mitochondrial Translocation of p53 Modulates Neuronal Fate by Preventing Differentiation-Induced Mitochondrial Stress - Xavier, Joana M. (Mary Ann Liebert, Inc., 2014)
Aims: Apoptosis regulatory proteins, such as p53, play a pivotal role in neural differentiation, through mechanisms independent of cell death. In addition, p53 has been identified as an important regulator of mitochondrial survival response, maintaining mitochondrial DNA (mtDNA) integrity and oxidative protection. The aim of this study was to determine the role of mitochondrial p53 in organelle damage and neural differentiation. Results: Our results show that mitochondrial apoptotic events such as reactive oxygen species production, mitochondrial membrane permeabilization, and cytochrome c release are typical of early-stage mouse neural stem cell differentiation, which occurs 3–18 h after induction of differentiation, with no evidence of cell death. In addition, decreased mtDNA content, lipidated LC3 (LC3-II), colocalization of mitochondria and LC3-II puncta, and mitochondria-associated Parkin are consistent with activation of mitophagy. Importantly, at early stages of neural differentiation, p53 was actively translocated to mitochondria and attenuated mitochondrial oxidative stress, cytochrome c release, and mitophagy. Forced mitochondrial translocation of p53 increased neurogenic potential and neurite outgrowth. Innovation and Conclusion: In conclusion, our results reveal a novel role for mitochondrial p53, which modulates mitochondrial damage and apoptosis-related events in the context of neural differentiation, thus enhancing neuronal fate. Antioxid. Redox Signal. 21, 1009–1024.